Potential enhancement of post-stroke angiogenic response by targeting the oligomeric aggregation of p53 protein - Tam, Hoi Hei; Zhu, Dongxing; Ho, Samuel Sze King; Vong, Heng Wai; Wong, Vincent Kam Wai; Mok, Simon Wing-Fai; Wong, Io Nam (Frontiers in Cellular Neuroscience, 2023)
Tumor suppressor gene p53 and its aggregate have been found to be involved in many angiogenesisrelated pathways. We explored the possible p53 aggregation formation mechanisms commonly occur after ischemic stroke, such as hypoxia and the presence of reactive oxygen species (ROS). The angiogenic pathways involving p53 mainly occur in nucleus or cytoplasm, with one exception that occurs in mitochondria. Considering the high mitochondrial density in brain and endothelial cells, we proposed that the cyclophilin D (CypD)-dependent vascular endothelial cell (VECs) necrosis pathway occurring in the mitochondria is one of the major factors that affects angiogenesis. Hence, targeting p53 aggregation, a key intermediate in the pathway, could be an alternative therapeutic target for post-stroke management.